Selection of native strains of Rhizobium leguminosarum bv phaseoli efficient in biological nitrogen fixation in Costa Rican soils. - Mora, Floribeth (Agronomía Mesoamericana, 2016)
One hundred and thirty one strains of R. leguminosarum bv phaseoli were isolated from different bean producing zones in Costa Rica. The response of its inoculation to the Huasteco Negro (Phaseolus vulgaris L.) bean variety was evaluated under green house conditions. Pots and heat treated soil were used. The seeds inoculation was conducted using a bacterial suspension of 10° ucf/ml, approximately. Besides, anabsolute control (without inoculation, without nitrogen) and a control with nitrogen (+ 140 kg N/ha) were included. The dry weight of the nodules, dry weight of the aerial part and the ureids concentration of the foliar area at the R6 stage ofdevelopment were the measured variables. The plants inoculated with the CR-455, CR-487 and CR-BSA strains showed the largest nodules’ dry weight values. The absolute control showed the lowest dry weight of nodules. Significant differences (P<0.05) were observed among so me treatments and the controls. The plants showing the highest foliar dry weight were those inoculated with the CR-482, CR-492, CR- 422 and CR-454 strains. Significant differences (P<0.05) were registered for the ureids concentrations among some treatments and the controls. The plants inoculated with the CR-475, CR- 492 and CR-422, CR-487 and CR-477 strains had the highest ureids concentrations and also showed the largest atmospheric nitrogen fixing capacity under green house conditions. A variation of the atmospheric nitrogen fixing capacity or effectiveness among some Rhizobium strains was observed, when comparing the results with the absolute and nitrogenous controls, which agrees with the bibliography.